Investigation of temperature characteristics of the glow discharge by molecular emission - Livia Mesarosh; Месарош Лівіа; Mészáros Lívia; Mikhailo Chuchman; Чучман Михайло; Alexander Shuaibov (Scientific and Technical Translations, 2021)
Abstract. The results of studies of the plasma of a glow discharge with liquid cathode at atmospheric pressure air are presented. The emission spectra of the glow discharge with an electrode based on distilled water at currents of 12 and 32 mA were obtained.
Keywords: temperature; glow discharge; plasma